2013
DOI: 10.4236/ojgen.2013.31005
|View full text |Cite
|
Sign up to set email alerts
|

FTO genotype is associated with body mass index and waist circumference in Mexican young adults

Abstract: Individual variations in the fat mass and obesityassociated (FTO) gene have been associated with obesity and BMI in diverse populations, but there are no reports in young Mexicans. We explored the association of a common FTO single-nucleotide polymorphism (SNP, rs805704) with obesity-related phenotypes in Mexican young adults. The FTO-SNP was genotyped using the fluorescent polarization method in college-age, apparently healthy subjects from the "UP AMIGOS" cohort (n = 251, 18 -25 yrs). Homozygotes for the A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…These results are consistent with those of previous studies suggesting the involvement of this gene in lipid metabolism [51, 52], obesity, T2DM [5154], and MS in different populations [5557]. Our sample size ( n  = 838) had power values of 72%, 74%, and 60% to detect associations between obesity status and rs3751812 (OR = 1.51), rs8050136 (OR = 1.52), and rs9939609 (OR = 1.44), respectively.…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with those of previous studies suggesting the involvement of this gene in lipid metabolism [51, 52], obesity, T2DM [5154], and MS in different populations [5557]. Our sample size ( n  = 838) had power values of 72%, 74%, and 60% to detect associations between obesity status and rs3751812 (OR = 1.51), rs8050136 (OR = 1.52), and rs9939609 (OR = 1.44), respectively.…”
Section: Discussionsupporting
confidence: 94%
“…SNP rs8057044 was associated with BMI, weight, and WC independent of age and sex in young adults from San Luis Potosí, México. AA homozygosity was associated with a higher mean BMI than AG/GG, but without reaching the BMI values of overweight or obesity (BMI > 25; Terán‐Garcia et al, ). Our study found an association of rs8057044 with overweight (up to BMI 95th percentile) only in boys, supporting the effect of this FTO SNP in making boys heavier, but not obese.…”
Section: Discussionmentioning
confidence: 98%
“…Particularly for Mexican admixed populations , the FTO rs8057044 SNP influences obesity‐related phenotypes in young Mexicans (Terán‐Garcia et al, ). FTO SNPs rs9939609, rs1421085 , and rs17817449 were associated with class III obesity in adults (Villalobos‐Comparán et al, ).…”
Section: Introductionmentioning
confidence: 99%